Analysis of Settlement’s Spread Pattern Based on Physiographic Condition in Nagari Balah Aie Timur Kecamatan VII Koto Sungai Sarik Kabupaten Padan Pariaman - Febrianto, Hary; Ismayani, Nina (Universitas Negeri Makassar, 2018)
The existing settlement patterns in Indonesia are generally divided into three types, namely linear pattern, radial pattern and a pattern of concentric circles which exist and are influenced by factors of natural resources or fisiografi. The pattern of the village or settlement is a settlement in the distribution of the specificity of the phenomenon of space or territory, against the peculiarities are the forms individually as well as settlement spread from individual neighborhood clusters. Climate factors, the State of the soil, the water, topography, availability of natural resources as well as the population in a region made the distinctiveness or character on settlement patterns at a village/nagari/head, it is interesting to know the pattern of the spread of settlements Nagari Balah Aie Aie Balah Eastern Nagari and, using the research method used for this research is a descriptive qualitative approach to case studies (case study) of distinct physiographic Shaper settlement patterns that exist in nagari such. The research results obtained from the research field that is viewed and measured settlements are there in 2 (two) the nagari namely Nagari Balah Aie and Aie Balah Eastern Nagari and on aspects of the existing fisiografi and Non-Fisiografi, and count formulas nearest neighbor (T = Ju/Jh), with the result declared distribution pattern of settlement in Nagari Balah Aie Aie Balah Eastern Nagari and